Strategy maps : converting intangible assets into tangible outcomes - Kaplan, Robert S.; Norton, David P., 1941- (Boston : Harvard Business School Press, 2004)
"Robert S. Kaplan and David P. Norton introduced a revolutionary performance measurement system called the Balanced Scorecard to enable companies to quantify critical intangibles such as people, information, and culture." "Based on their work with more than 300 organizations spanning over a dozen years, Kaplan and Norton have created a new tool that has turned out to be as important an innovation as the Balanced Scorecard itself: strategy maps.
Just as you can't manage what you can't measure, say Kaplan and Norton, you can't measure what you can't describe." "Providing the missing link between strategy formulation and implementation, Strategy Maps is a blueprint for describing, measuring, and aligning intangible assets for superior performance."--BOOK JACKET.
Strategy maps -- Operations management processes -- Customer management processes --Innovation processes -- Regulatory and social processes -- Aligning intangible assets to enterprise strategy -- Human capital readiness -- Information capital readiness -- Organization capital readiness -- Customizing your strategy map to your strategy -- Planning the campaign -- Private-sector organizations -- Public-sector organizations -- Nonprofit organizations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Strategic planning; Intangible property -- Management; Human capital; Management; Strategische planning; Organisatieontwikkeling; Management; Human Capital; Planification stratégique; Biens incorporels -- Gestion; Ressources humaines; Gestion; Tableau de bord prospectif; Gestion du personnel; Planification stratégique; Investissement immatériel; Erweiterung; Strategisches Management; Immaterielles Wirtschaftsgut; Balanced Scorecard; Human capital; Intangible property -- Management; Management; Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books